Toward Hyperpolarized 19F Molecular Imaging via Reversible Exchange with Parahydrogen. Issue 15 (13th June 2017) - Shchepin, Roman V.; Goodson, Boyd M.; Theis, Thomas; Warren, Warren S.; Chekmenev, Eduard Y.
Abstract: Fluorine‐19 has high NMR detection sensitivity—similar to that of protons—owing to its large gyromagnetic ratio and high natural abundance (100 %). Unlike protons, however, fluorine‐19 ( 19 F) has a negligible occurrence in biological objects, as well as a more sensitive chemical shift. As a result, in vivo 19 F NMR spectroscopy and MR imaging offer advantages of negligible background signal and sensitive reporting of the local molecular environment. Here we report on NMR hyperpolarization of 19 F nuclei using reversible exchange reactions with parahydrogen gas as the source of nuclear spin order. NMR signals of 3‐fluoropyridine were enhanced by ≈100 fold, corresponding to 0.3 % 19 F nuclear spin polarization (at 9.4 T), using about 50 % parahydrogen. While future optimization efforts will likely significantly increase the hyperpolarization levels, we already demonstrate the utility of 19 F hyperpolarization for high‐resolution hyperpolarized 19 F imaging and hyperpolarized 19 F pH sensing. Abstract : NMR signals of 3‐fluoropyridine are enhanced by ≈100‐fold, corresponding to 0.3 % nuclear spin polarization (at 9.4 T), using 50 % parahydrogen. While future optimization efforts can further increase the efficiency of 19 F hyperpolarization (i.e. in excess of 20 % using the presented approach), the authors demonstrate the potential of this technology on pioneering examples of high‐resolution hyperpolarized 19 F imaging and hyperpolarized 19 F pH sensing.